Temporal-order judgment of visual and auditory stimuli: modulations in situations with and without stimulus discrimination - Hendrich, Elisabeth; Strobach, Tilo; Buss, Martin; Mueller, Hermann J.; Schubert, Torsten (Frontiers in Integrative Neuroscience, 2012)
Temporal-order judgment (TOJ) tasks are an important paradigm to investigate processing times of information in different modalities. There are a lot of studies on how temporal order decisions can be influenced by stimuli characteristics. However, so far it has not been investigated whether the addition of a choice reaction time task has an influence on temporal-order judgment. Moreover, it is not known when during processing the decision about the temporal order of two stimuli is made. We investigated the first of these two questions by comparing a regular TOJ task with a dual task. In both tasks, we manipulated different processing stages to investigate whether the manipulations have an influence on temporal-order judgment and to determine thereby the time of processing at which the decision about temporal order is made. The results show that the addition of a choice reaction time task does have an influence on the temporal-order judgment, but the influence seems to be linked to the kind of manipulation of the processing stages that is used. The results of the manipulations indicate that the temporal order decision in the dual task paradigm is made after perceptual processing of the stimuli.